Review of Adoption and Impact Assessment on Conservation Agriculture in Ethiopia - Chaka Gameda; Fikiru Temesgen Gelata; HAN Jiqin (International Journal of Marketing & Human Resource Research, 2022)
Conservation agriculture plays a great role in improving farming land productivity and mitigating climate change impact. It is a concept for resource-saving agricultural crop production that strives to achieve acceptable profits together with high and sustained production levels while concurrently conserving the environment. The paper initially investigates theoretical concepts of conservation agriculture in Ethiopia. It then reviews the adaptation level of conservation agriculture by farm households and its impact on their productivity. The various challenges for the adoption of Conservation agriculture are lack of knowledge in CA at the expertise and farmers' level; the belief of farmers on tillage, technical, social, financial, and policy issues; the market does not supply them with the necessary seeds to carry out intercropping; high input costs, low input availability, and associated high opportunity costs for crop residue; and also lack biomass and residues. Its major impacts are increased labor productivity at the time of soil preparation; it helps with water harvesting strategy; the benefit of crop residue retention is a higher content of organic matter in the soil and higher water infiltration rates, which reduces surface runoff and soil erosion significantly.